Prognostic Nutritional Index and Systemic Immune-inflammation Index: Possible New Parameters for COVID-19 Severity - Suyoso, Suyoso; Oehadian, Amaylia; Khotijah, Alfreda Amelia; Marthoenis, Marthoenis (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: The prognostic nutritional index (PNI) parameter has been widely used in estimating the severity of COVID-19. In contrast, investigating the role of the systemic immune-inflammation index (SII) in determining the COVID-19 severity is prospective. This study aimed to investigate the potential of PNI and SII parameters to distinguish the severity of symptoms of COVID-19.Methods: A retrospective observational study was conducted among 209 hospitalized patients with COVID-19. Data were collected from August 2021 to February 2022 in Indonesia’s general COVID-19 referral hospital. Demographic and laboratory data, including PNI and SII, were analyzed and compared between the severe and non-severe symptoms of COVID-19 patients. The statistical analysis of the receiver operating characteristic curve (ROC) and area under curve (AUC) was conducted to predict the potential of these parameters in distinguishing the COVID-19 severity. Results: More than half of this study’s patients (54.55%) were non-severe COVID-19. The SII values in patients with severe symptoms were significantly higher than in those with non-severe symptoms (2,445.24 vs. 1,423.28, p=0.005). In contrast, the PNI value in patients with severe COVID-19 symptoms was significantly lower than those with non-severe symptoms (38.04 vs. 33.93, p<0.001). The area under the curve (AUC) value of PNI was 0.694, meanwhile the SII was 0.635. The optimum cut-off for the PNI was <35.407, whereas the SII was >2,212.787. PNI and SII were the potential new diagnostic parameters for COVID-19 severity.Conclusion: PNI and SII parameters can potentially distinguish the severity of symptoms of COVID-19.